(untitled) (Revista de História Regional, 2025)
The article addresses the role played by rural schools and Brazilian peasant social movements in confronting the coloniality of knowledge. The importance of this discussion lies in the global environmental, social, and food crisis and how coloniality contributes to the worsening of this situation. The research question is: How do rural schools in Brazil contribute to resisting the coloniality of knowledge and valuing local knowledge, especially in the food and educational practices of rural communities? The central objective of the study is to discuss the role of rural schools in resisting the coloniality of knowledge in the Global South. To this end, we propose an exploratory methodology using bibliographic resources. It was concluded that Brazilian rural schools can contribute to resisting the coloniality of knowledge and valuing local knowledge in the face of contemporary reality through a liberating and decolonial education that breaks with hegemonic forms of land exploitation and promotes a healthier and more environmentally viable relationship in food production and consumption.